Validating policy prescription from benefit-cost assessments of mining through comparative analysis and test hypotheses - Boquiren, Arturo C. ([Quezon City] School of Economics, University of the Philippines, 2008)
The paper proposes that benefit-cost analyses of mining be validated by comparative analyses and tests of hypotheses. Mining and non-mining communities can be compared to assess the contribution of mining to development. Further, tests of hypotheses can be used to determine whether mining communities are significantly different from non-mining communities in terms of poverty rates, health indicators, education, and other social indicators. Applying the said techniques in Benguet, Northern Philippines, the author found that mining communities, despite several years of mining operations, are not significantly different from non-mining communities.
Title was 'Philippine Review of Business and Economics' until 1979. Title changed to 'Philippine Review of Economics and Business' from 1980-2000, and again changed to 'Philippine Review of Economics' since 2001.
This paper was presented in the November 2007 annual meeting of the Philippine Economic Society and before an international conference and non-government organizations in the same month.
Keywords: Mineral industries -- Philippines -- Benguet; Mineral industries -- Philippines -- Benguet -- Economic aspects